Systematic Review of Blockchain Technology in Electronic Medical Record Management: Trends, Challenges, and Future Research Directions - Irmayanti, Hani; Atin, Sufa; Heryandi, Andri; Afrianto, Irawan; Rijanto, Estiko; Dwiguna Sumitra, Irfan (Universitas Komputer Indonesia, 2026)
This study explores the role of blockchain technology in addressing security and integration challenges within Electronic Medical Record (EMR) systems. Using a Systematic Literature Review (SLR) of 143 selected articles, the research highlights blockchain’s potential to provide decentralized, transparent, and secure data exchange. Key findings indicate that permissioned blockchains, specifically Hyperledger Fabric, are preferred for maintaining data integrity and managing access via smart contracts. To handle big data scalability, the study recommends a hybrid architecture, while identifying the integration of AI and IoT as the future of